Digital-Based Marketing Training in Improving Online Business Sales to MSMES in Cisewu Village, Garut Regency, Indonesia - Grida Saktian Laksito (Research Collaboration Community (RCC), 2021)
The purpose of this community service is to assist business actors in providing Digital-Based Marketing Training to increase product sales online at MSMEs in Cisweu Village, Cisewu District, Garut Regency. This method of community service activity begins with the preparation stage and field survey. This survey stage begins with direct discussions with the Village Head in Cisewu Village, Cisewu District, Garut Regency to identify the needs, opportunities, and challenges faced by MSME business actors in Ciseweu Village, after knowing what things are needed then carry out the socialization and training stage. made by the team. The results of this study are the knowledge of participants who are residents and MSME business actors in Cisewu Village from RT 001-005/RW 002 Cisewu District regarding digital-based marketing before PKM activities, the majority of participants are in the category of not understanding digital business. After the PKM activities were carried out and the material presentation was delivered, the MSME training succeeded in providing participants with increasing knowledge about digital business.